Performance and emission properties of preheated and blended fennel vegetable oil in a coated diesel engine - Hazar, Hanbey; Sevinc, Huseyin; Sap, Serhat (Elsevier Sci Ltd, 2019)
The use of crude fennel seed oil in a diesel engine, whose combustion chamber was thermally insulated, with diesel fuel at specific rates was investigated in the present study. A single-cylinder air cooled diesel engine was used as the test engine. Plasma spray method (coated with Cr3C2 in a thickness of 300 mu m) was used as the coating method. Since the atomisation and vaporisation of fennel oil are highly affected by the physical properties of the fuel, a preheating process of 100 degrees C was applied. Crude fennel oil mixed with diesel fuel at 30% and 50% by volume. It was shown that a preheating process of 100 degrees C provided a proper fuel flow and reduced the viscosity of the funnel oil and additionally, the coating process decreased carbon monoxide (CO), smoke, and hydrocarbon (HC) emissions but increased nitrogen oxides (NOx), thermal efficiency, and exhaust gas temperature (EGT).
Fuels, Combustion, Engines and Fire Conference (FCE) / International Combustion Symposium (ICS) -- MAR 10-19, 2019 -- Antalya, TURKEY
Keywords: Preheated fennel seed oil; Insulated diesel engine; Exhaust emission; Engine performance